Risk Factors of Microscopically Tumor-Free Surgical Margins for Recurrence and Survival of Oral Squamous Cell Carcinoma Patients - Pei, Meiling; Han, Dawool; Kim, Ki-Yeol; Kim, Dong Wook; Nam, Woong; Kim, Hyung Jun; Cho, Eunae Sandra; Kim, Hyun Sil; Cha, In-Ho; Zhang, Xianglan (Frontiers in Oncology, 2022)
Objectives: The concept of adequate surgical margins remains controversial in oral squamous cell carcinoma (OSCC) surgery. This study aimed to identify surgical margin-related indicators that might impact recurrence and survival of OSCC patients. Materials and Methods: Histopathological examination was performed using hematoxylin-eosin-stained surgical margin tissue sections in 235 OSCC patients. Axin2 and Snail expression at the surgical margin was detected by immunohistochemistry. The impact of the Axin2-Snail cascade on tumorigenesis of the immortalized human oral keratinocyte (IHOK) line was investigated in vivo. Results: The width and dysplasia of surgical margins were not significantly associated with the outcome of OSCC patients. In a multivariate analysis using variable clinicopathologic factors and with Axin2 and Snail expression as cofactors, higher age (hazard ratio [HR]:1.050; P=0.047), Axin2 (HR:6.883; P=0.014), and Snail abundance (HR:5.663; P=0.009) had independent impacts on worsened overall survival. Similarly, lesion site in retromolar trigone (HR:4.077; P=0.010), upper (HR:4.332; P=0.005) and lower gingiva (HR:3.545; P=0.012), presence of extranodal extension (HR:9.967; P<0.001), perineural invasion (HR:3.627; P=0.024), and Snail abundance (HR:3.587; P<0.001) had independent impacts on worsened recurrence-free survival. Furthermore, Axin2 knockdown induced decreased Snail expression and attenuated tumorigenesis in the IHOK line. Conclusion: Histopathological examination of surgical margins may not be reliable to predict OSCC patient outcome. Molecular analysis may provide a more accurate risk assessment of surgical margins in OSCC. In particular, Axin2 and Snail are potential predictive biomarkers for the risk assessment of surgical margins in OSCC.